MODE OF INHERITANCE OF PATIENTS WITH FAMILIAL MEDITERRANEAN FEVERIN OUR CLINIC - Yusuf BAYRAKTAR; Nilgün M. SAYINALP; Esin ÖZYILKAN; Burhan KAYHAN; Sevim BALCI; Hasan TELATAR (Turkish Journal of Gastroenterology, 2020)
-